Metafiction in Postmodernist Literature: Breaking the Fourth Wall - Masood, Waniya; Choudhary, Arooba (Pakistan Languages and Humanities Review, 2025)
The primary intent of this research is to investigate how “fourth wall” is broken in the postmodernist literature through metafiction. There has been a postmodern critique on the grand narratives through metafiction. This study incorporates a comparative method to explore how authors like Jorge Luis Borges, John Barth, and Thomas Pynchon experiment storytelling techniques which exposed the artificial nature of the narrative. Additionally, the paper examines using critical discourse analysis how narrative and the audience are exposed to each other making the literary texts more expository and explanatory rather than convoluted. It employs Linda Hutcheon’s understanding of postmodern metafiction to demonstrate how metafiction subverts reality in fiction. The research affirms the significance of meaning that arises from the interaction of the audience with the narrative through metafiction in postmodernist literature. The study proposes a new perspective and approach to the transformative paradigm of intertextuality and fictional world.